2014
DOI: 10.1183/09031936.00063914
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgA production by B-cells in COPDvialung epithelial interleukin-6 and TACI pathways

Abstract: Despite their relevance to mucosal defense, production of IgA and the function of lung B-cells remain unknown in chronic obstructive pulmonary disease (COPD).We assessed IgA synthesis in the lungs of COPD (n=28) and control (n=21) patients, and regulation of B-cells co-cultured with in vitro-reconstituted airway epithelium.In COPD lung tissue, synthesis of IgA1 was increased, which led to its accumulation in subepithelial areas. In vitro, the COPD bronchial epithelium imprinted normal human B-cells for increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 45 publications
3
37
0
1
Order By: Relevance
“…influenzae colonisation of the airways despite the presence of specific IgA and IgG in the serum and sputum of COPD patients. More recently, Polosukhin[7] described a defect in sIgA distribution in BAL fluid from severe COPD patients, whilst in contrast IgA synthesis and accumulation was shown to be increased in COPD lung tissue[12]. Our data of increased IgA and sIgA in the COPD airway compared to health would support the observations of Groeneveld[11] and Ledjemi[12].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…influenzae colonisation of the airways despite the presence of specific IgA and IgG in the serum and sputum of COPD patients. More recently, Polosukhin[7] described a defect in sIgA distribution in BAL fluid from severe COPD patients, whilst in contrast IgA synthesis and accumulation was shown to be increased in COPD lung tissue[12]. Our data of increased IgA and sIgA in the COPD airway compared to health would support the observations of Groeneveld[11] and Ledjemi[12].…”
Section: Discussionsupporting
confidence: 88%
“…There are conflicting previous reports of both decreased sIgA[7] and increased IgA[12] in the COPD airway. We therefore assessed both total and secretory IgA in BAL (Fig 2A and 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been shown in asthma that BECs may suppress constitutive and IgE-dependent histamine release by lung mast cells [10], further highlighting the central role of the epithelium in sensing and shaping mucosal danger signalling. We recently showed that BECs from COPD patients also imprint B-cells with signals promoting maturation into IgA-producing plasma cells, while cigarette smoke partly counteracts this IgA-promoting effect [11]. This effect was at least partly related to an intrinsic ability of COPD BECs to produce increased amounts of certain cytokines (IL-6 and BAFF; B-cell activating factor) and to induce B-cell expression of TACI (transmembrane activator and CAML interactor).…”
mentioning
confidence: 99%